Factors contributing to Zakat compliance behaviour among employees in Melaka, Malaysia - Sheikh Mokhtar, Siti Salwa (2018)
The study examines the factors that contribute towards Zakat compliance behaviour among employees in Melaka by combining the theories of Theory of Planned Behaviour and the measurement of Muslim Religiosity Personality Inventory. Previous research proved that even though the collection of Zakat increased, the collection was still not at par with expected collection which reflects that there is a huge gap that needed to be covered in terms of distribution for the needy. Hence, a survey method is used with a total of 217 questionnaires are coded to measure the four variables which are Attitude, Perceived Behavioural Control, Subjective Norm and Religiosity which included both public and private sectors employees in Melaka. Based on the obtained result, Attitude and Perceive Behavioural Control are significant towards Zakat compliance behaviour. However, Subjective Norm and Religiosity are not significant towards Zakat compliance behaviour. This study will benefit the nation by enhancing the Zakat institution; improve ways to increase Zakat collection by focusing on specific group in order to increase the behaviour of Zakat payment. Moreover, proper ways to increase the understanding of Zakat among community can be developed as well as increasing contribution of Zakat collection.